Pengaruh Media Sosial Instagram dan E-Wom (Electronic Word of Mouth) Terhadap Keputusan Pembelian Konsumen - Muhamad Sahal Mahpud; Leny Muniroh; Hendri Maulana (Indonesian Journal of Innovation Multidisipliner Research, 2024)
This study aims to determine the effect of Instagram Social Media and E-WOM (Electronic Word Of Mouth) on Purchasing Decisions of Ruby UMKM consumers. The research method used is an expalani survey method with a quantitative approach. The population in this study were 100 respondents who followed the Instagram account "amorebyruby". This research instrument is a questionnaire. The results of the research instrument test used multiple regression analysis tests, t tests, f tests. The results of the analysis show that Instagram Social Media and E-WOM have a significant effect on Purchasing Decisions with the results of multiple regression analysis tests. The results of the Instagram t test obtained the results of the t test> t table (2.305> 1.985) means that Ho1 is rejected Ha1 is accepted, the E-WOM t test obtained the results (7.632> 1.985) means Ho2 is rejected and Ha2 is accepted, and the f test results are (37.476> 3.090) meaning Ho3 is rejected Ha3 is accepted. Based on the results of this data, it can be concluded that Instagram Social Media and E-WOM simultaneously influence consumer purchasing decisions at Ruby MSMEs.